Analisis Pengaruh Efikasi Diri dan Dukungan Sosial terhadap Grit Mahasiswa Universitas Buana Perjuangan Karawang - Ilham Muhsin Nururrozi; Lania Muharsih; Yulyanti Minarsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
University students are faced with various academic, social, and psychological challenges that require resilience and strong perseverance as essential factors to complete their education and achieve academic success. This study aims to analyze the influence of self-efficacy and social support on grit among students at Buana Perjuangan University Karawang. The high rate of students failing to graduate on time and their low enthusiasm in facing academic challenges are important issues that need to be examined. This study uses a quantitative method with a causal design. Data were collected from 386 students at Buana Perjuangan University Karawang who were selected using convenience sampling. The instruments used were the Short Grit Scale (Grit-S) to measure grit, the General Self-Efficacy Scale (GSES) to measure self-efficacy, and the Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support. Data analysis was performed using multiple regression with SPSS 26.0 software. The results showed that both self-efficacy and social support had a significant partial and simultaneous effect on student grit. These findings supported the research hypothesis and were supported by an R Square value of 0.414, indicating that 41.4% of the variation in grit could be explained by self-efficacy and social support simultaneously, while the remaining 58.6% was influenced by other factors. These findings reinforce the idea that interventions focused on strengthening self-confidence and providing external social support will be effective in increasing students' grit.